2012
DOI: 10.1530/eje-12-0447
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and metabolic parameters are associated with variation in thyroid hormone levels among euthyroid young men

Abstract: Objective: Thyroid disorders affect metabolism and body composition. Existing literature has been conflicting on whether this is also the case for thyroid hormone levels within the euthyroid range. Therefore, we have investigated the relationship between thyroid hormone concentrations and body composition together with metabolic parameters in a population of healthy euthyroid men. Methods: Healthy male siblings (nZ941, 25-45 years, median BMI 24.6) were recruited in a cross-sectional, population-based study; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 41 publications
(62 reference statements)
9
111
3
Order By: Relevance
“…Interdependency between serum leptin and TH concentrations is assumed to be mediated by a complex interplay with TSH, further involving thyrotropin-releasing hormone (46,47). In concordance, a recent study on young men provided evidence for a link between serum TSH and leptin concentrations, even in the euthyroid state (48). In recognition of these results, we tested for a possible effect of TSH on the association between 3,5-T2 and leptin.…”
Section: Figmentioning
confidence: 73%
“…Interdependency between serum leptin and TH concentrations is assumed to be mediated by a complex interplay with TSH, further involving thyrotropin-releasing hormone (46,47). In concordance, a recent study on young men provided evidence for a link between serum TSH and leptin concentrations, even in the euthyroid state (48). In recognition of these results, we tested for a possible effect of TSH on the association between 3,5-T2 and leptin.…”
Section: Figmentioning
confidence: 73%
“…Given the role of thyroid hormones in the regulation of energy expenditure and thermogenesis (40), and the increasingly well-established relations between subtle alterations in TSH, thyroid hormone levels, and cardiometabolic risk factors (13,(17)(18)(19)(20)(21)23,24,28,29,35), there has been interest in assessing the effects of weight loss on thyroid hormone levels. In a study of adult overweight or obese otherwise healthy subjects undergoing a controlled lifestyle modification program, modest weight loss (6.5 -1.0%) resulted in reductions in TT3 without significant changes in TSH or fT4.…”
Section: Discussionmentioning
confidence: 99%
“…The present assessment of an unselected U.S. population (by default devoid of specific clinical indications for testing) minimizes the risk of selection bias. While other published analyses of population databases have not addressed any potential racial or ethnic differences (10,11,(17)(18)(19)21,(23)(24)(25)28,29), this NHANES cohort consisted of participants who predominantly selfidentified as non-Hispanic white, non-Hispanic black, Mexican-American, or other Hispanic. The lack of any race/ ethnicity differences in TSH and thyroid hormones suggests that with respect to race/ethnicity, other factors such as BMI (which did show ethnicity differences in the analysis) still play a greater role than the thyroid axis in determining overall cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests an individual set point for pituitary-thyroid axis function (1). We and others have shown that this between-subject variation in TH levels, although within the normal range, is nevertheless associated with a number of clinical parameters such as bone mass, BMI, metabolic indices, and heart rate (2,3,4,5). The physiological basis of the set point of this axis is poorly understood (6).…”
Section: Introductionmentioning
confidence: 98%